A case report of chromosome 17q22‐qter trisomy with distinct clinical presentation and review of the literature. Issue 4 (14th February 2018) - Upadia, Jariya; Philips, Joseph B.; Robin, Nathaniel H.; Lose, Edward J.; Mikhail, Fady M.
Key Clinical Message: Terminal 17q trisomy is very rare but a recognizable genetic syndrome. The majority of cases reported are inherited from a balanced translocation carrier. This syndrome involves many organs and the severity ranges from mild to severe depending on the size of the 17q gain. Abstract : Terminal 17q trisomy is very rare but a recognizable genetic syndrome. The majority of cases reported are inherited from a balanced translocation carrier. This syndrome involves many organs and the severity ranges from mild to severe depending on the size of the 17q gain.